2006
DOI: 10.3390/i7070204
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin-3-Gallate Ameliorates Alcohol-Induced Liver Injury in Rats

Abstract: Endotoxemia is a common event in alcoholic liver disease. Elevated intestinal permeability is the major factor involved in the mechanism of alcoholic endotoxemia and the pathogenesis of alcoholic liver disease. This study examined the effect of epigallocatechin-3-gallate (EGCG) on alcohol-induced gut leakiness, and explored the related mechanisms involved in its protection against alcohol-induced liver injury in rats. Four groups of female Sprague-Dawley rats were studied. Alcohol and alcohol/EGCG groups rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 36 publications
1
20
0
2
Order By: Relevance
“…TNF-α is one of the most important inflammatory mediator produced in the initial step of several models of hepatotoxicity. Also, the role of nitric oxide in hepatotoxicity was confirmed by showing increased level of stable metabolites of nitric oxide including nitrites and nitrates ( 3 5 7 8 29 ). Indeed, nitric oxide in combination with oxygen radicals could form peroxynitrite that is known as the most potent oxidants that contribute in oxidative damage to cells and tissues.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…TNF-α is one of the most important inflammatory mediator produced in the initial step of several models of hepatotoxicity. Also, the role of nitric oxide in hepatotoxicity was confirmed by showing increased level of stable metabolites of nitric oxide including nitrites and nitrates ( 3 5 7 8 29 ). Indeed, nitric oxide in combination with oxygen radicals could form peroxynitrite that is known as the most potent oxidants that contribute in oxidative damage to cells and tissues.…”
Section: Discussionmentioning
confidence: 95%
“…Damage to lipid membrane and DNA due to oxidative stress could finally lead to cell death and tissue damage. On the other hand, alcohol-induced oxidative stress in liver tissue could promote hepatic inflammation ( 8 ). Another suggested mechanism for ethanol hepatotoxicity is the increased expression of inflammatory mediators such as TNF-α.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alcohol induces damage by building up endotoxin mediated oxidative stress in the cellular constituents of the tissue. Catechins including EGCG have been demonstrated previously by us [11, 12] and others [13, 14] to attenuate alcoholic liver injury by creating an antioxidant- oxidant balance in the hepatic tissues. ALD is also accompanied by elevated intestinal permeability which can be abridged by probiotic administration.…”
Section: Introductionmentioning
confidence: 96%
“…The protective effects of antioxidant rich natural compounds against different toxicant mediated tissue injury has been identified in many studies [13] , [14] , [15] . In specific, numerous studies have demonstrated the protective effects of antioxidants such as pumpkin oil [16] , resveratrol [17] , curcumin [18] , quercetin [19] and epigallocatechin-3-gallate [20] against alcohol induced tissue injury.…”
Section: Introductionmentioning
confidence: 99%